Pelatihan Tes Kemampuan Akademik (TKA) Matematika bagi Siswa SMA/MA Kelas XII di Daerah Istimewa Yogyakarta (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2026)
The government's implementation of the Academic Ability Test (TKA) has shocked some students, particularly because they are unfamiliar with the test questions. This highlights the need for public awareness campaigns regarding the TKA questions, particularly in private schools. This community service initiative aims to provide high school students in the Special Region of Yogyakarta (DIY) with an overview of the TKA mathematics exam. The method used in this initiative is drills and discussions, aimed at training and preparing students for the types of questions tested in the TKA. This initiative was attended by five private schools in the Special Region of Yogyakarta and conducted by lecturers and students from the Mathematics Education study program at Alma Ata University. The results of this training indicate that students gained an overview of the TKA mathematics exam questions and learned several strategies for solving them effectively. This initiative is expected to help students become more prepared and confident in facing the TKA in the future.